2017
DOI: 10.1093/ofid/ofx080
|View full text |Cite
|
Sign up to set email alerts
|

Choosing Wisely Overnight? Residents’ Approach to Fever

Abstract: We surveyed internal medicine residents regarding how they approach febrile patients in cross-cover settings. Residents frequently use the term “full fever work-up,” and rely on this for sign-out. Despite this, residents felt fever work-ups were not evidenced-based, and definitions of when and how to respond to a fever varied.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…19,20 Such practice is even more pronounced in academic centers most cultures are ordered by trainees. 21 A prospective survey of internal medicine residents showed that trainees practice panculturing as a reflexive response to fever knowing that it is not evidence based or cost-effective. 21 Re-evaluation of the role of fever as a prompt for culturing, especially without consideration of focused, site-specific signs or symptoms, is needed to decrease overdiagnosis of infections such VAP.…”
Section: Discussionmentioning
confidence: 99%
“…19,20 Such practice is even more pronounced in academic centers most cultures are ordered by trainees. 21 A prospective survey of internal medicine residents showed that trainees practice panculturing as a reflexive response to fever knowing that it is not evidence based or cost-effective. 21 Re-evaluation of the role of fever as a prompt for culturing, especially without consideration of focused, site-specific signs or symptoms, is needed to decrease overdiagnosis of infections such VAP.…”
Section: Discussionmentioning
confidence: 99%
“…[ 12 ] This practice of reflexive blood culture ordering was found to be more prevalent among cross-covering residents at night shift. [ 23 , 24 ] Potential explanation for this observation in the survey include fewer staffing and supervision, and less familiarity with the patients during night shifts and on the weekends. [ 25 ] Our study expands on previous studies [ 12 , 13 ] by providing a better understanding on how variation in shift work and day of the week may influence the clinical decision making around blood culture.…”
Section: Discussionmentioning
confidence: 99%
“…We designed the chart abstraction instrument based on our prior survey [12]. We collected data on patient demographics and comorbidities, history of bacteremia, vital signs at the time of fever, tests ordered, documentation performed, documentation of bedside evaluation, cause of fever in progress notes, complications after fever, blood culture results, and 30-day mortality.…”
Section: Chart Abstractionmentioning
confidence: 99%
“…At the study institution, the sign-out provides guidance regarding performing a "full fever work-up" (FFWU), although its definition is not standardized. In a recent survey of residents, we found that almost all residents included blood cultures, urine studies, and a chest X-ray in the FFWU, but over half included at least one additional test [12]. In this study, we aimed to delineate what diagnostic tests overnight residents order in response to fevers and what sign-out, patient, and clinical factors influence ordering practices.…”
Section: Introductionmentioning
confidence: 99%